2011
DOI: 10.1093/glycob/cwr097
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of BRI2 on asparagine 170 is involved in its trafficking to the cell surface but not in its processing by furin or ADAM10

Abstract: Two different mutated forms of BRI2 protein are linked with familial British and Danish dementias, which present neuropathological similarities with Alzheimer's disease. BRI2 is a type II transmembrane protein that is trafficked through the secretory pathway to the cell surface and is processed by furin and ADAM10 (a disintegrin and metalloproteinase domain 10) to release secreted fragments of unknown function. Its apparent molecular mass (42-44 kDa) is significantly higher than that predicted by the number an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Vice versa, some glycosylation sites seem to be crucial for protein folding but their removal from folded proteins often does not affect the protein fold and function (Shental-Bechor and Levy, 2008). We observed that mutagenesis of Asn 170 had no remarkable effect on wild-type and mutant BRI 2 processing by PCs or ADAM10 but leads to the intracellular accumulation of BRI 2 as previously reported (Tsachaki et al, 2011). Wild-type BRI 2 with the N170A substitution accumulated in a Golgi compartment, similarly to the FBD and FDD mutant forms of BRI 2 , suggesting that glycosylation plays an important role in protein trafficking of BRI 2 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Vice versa, some glycosylation sites seem to be crucial for protein folding but their removal from folded proteins often does not affect the protein fold and function (Shental-Bechor and Levy, 2008). We observed that mutagenesis of Asn 170 had no remarkable effect on wild-type and mutant BRI 2 processing by PCs or ADAM10 but leads to the intracellular accumulation of BRI 2 as previously reported (Tsachaki et al, 2011). Wild-type BRI 2 with the N170A substitution accumulated in a Golgi compartment, similarly to the FBD and FDD mutant forms of BRI 2 , suggesting that glycosylation plays an important role in protein trafficking of BRI 2 .…”
Section: Discussionsupporting
confidence: 87%
“…Disulfide-bonded loops within pro-proteins and neuropeptides have been shown to be important for sorting of peptides from the trans-Golgi network to regulated secretory pathway (Glombik et al,1999; Krömer et al,1998). BRI 2 has a single N-linked glycosylation site (Asp170) inside the BRICHOS domain that has been shown in vitro to be important for BRI 2 trafficking to the cell surface and its steady state levels at the plasma membrane (Tsachaki et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Northern blotting identifies two transcripts, 1200 nt and 1700 nt long, respectively, originating from poly(A) signals at positions 1114 and 1593 [12]. The apparent molecular mass of the ITM2B protein (42–44 kDa) is higher than predicted from the number and composition of amino acids, suggesting that it is glycosylated [27]. It is a substrate for regulated intramural proteolysis and is processed by furin and ADAM10 (a disintegrin and metalloproteinase domain 10) as well as other proteases in a fashion similar to Notch to release secreted fragments [26].…”
Section: Discussionmentioning
confidence: 99%
“…The Bri23 peptide has been proposed to interact with Aβ42 and prevent its aggregation [83], and the Bri2 BRICHOS domain can bind the Bri23 according to mass spectrometry analysis [57]. Bri2 includes one glycosylation site at Asn170, and N-glycosylation has been shown to be important for Bri2 localization at the plasma membrane [84]. The mBri2 can be further processed in the TM region by a signal peptidase like enzyme (SPPL2), and shedding of the extracellular domain including the BRICHOS domain by ADAM10 suggests a physiological extracellular role for the BRICHOS domain [85].…”
Section: Bri Protein Familymentioning
confidence: 99%